2021
DOI: 10.1109/access.2021.3095339
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Machine Learning Techniques for Predicting Nha Trang Shorelines

Abstract: Nha Trang Coast is located in the South Central Vietnam and the coastal erosion has been occurring rapidly in recent years. Hence it is crucial to accurately monitor the shoreline changes for better coastal management and reduction of risks for communities. In this paper, we explored, for the first time, a statistical forecasting model, Seasonal Auto-regressive Integrated Moving Average (SARIMA), and two Machine Learning (ML) models, Neural Network Auto-Regression (NNAR) and Long Short-Term Memory (LSTM), to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The LSTM method also showed better accuracy than the Empirical Orthogonal Function (EOF) method in predicting shoreline change of Nha Trang Coast in South Central Vietnam. Further, the method was also in good agreement compared with Seasonal Auto-regressive Integrated Moving Average (SARIMA) and Neural Network Auto-Regression (NNAR) [6].…”
Section: Introductionmentioning
confidence: 83%
“…The LSTM method also showed better accuracy than the Empirical Orthogonal Function (EOF) method in predicting shoreline change of Nha Trang Coast in South Central Vietnam. Further, the method was also in good agreement compared with Seasonal Auto-regressive Integrated Moving Average (SARIMA) and Neural Network Auto-Regression (NNAR) [6].…”
Section: Introductionmentioning
confidence: 83%
“…In this paper, the transformer model is compared with a machine learning method SVR and a deep learning method LSTM, which have been proven to be robust coastline prediction methods [31,64].…”
Section: Training Strategies Of Svr Lstm and Transformer Methodsmentioning
confidence: 99%
“…The results showed that the ARIMA and LSTM techniques are both suitable for short-term coastline prediction in Akpakpa. In addition, YIN, ANH, and MAI [31] used NNAR and LSTM methods to predict coastline changes in surveillance camera images, and the LSTM model was employed to overcome the gradient disappearance and explosion problems of recurrent neural networks (RNNs). In conclusion, these models are effective at detecting coastline changes but still lack long-term time-series data learning dependencies for coastline prediction.…”
Section: Introductionmentioning
confidence: 99%